The transcriptional mechanism behind Mimosa pudica leaf folding in response to mechanical disturbance - Matteo Buti; Alice Checcucci; Chiara Vergata; Luciana Renna; Susanna Pollastri; Francesco Loreto; Stefano Mancuso; Federico Martinelli (Planta, 2025)
Main conclusions Repeated stress in Mimosa pudica reduces photosystem efficiency, alters gene expression, shifting from flavonoid biosynthesis to stress resistance pathways, offering insights for sustainable plant stress defense strategies. Abstract Mimosa pudica is a plant known for its ability to fold leaves in response to mechanical disturbances, which serves as a visible phenotypic stress marker. Leaf folding response occurs with a timing and an intensity that vary depending on the stimulus. This adaptive behavior may function as a defense mechanism, helping plant resist herbivores and environmental stressors. In this study, we investigated the gene regulatory networks underlying M. pudica leaf closure following single and multiple mechanical disturbances (whole pot drops). Chlorophyll fluorescence was measured as fast phenotypic indicator of transient or permanent photochemical damage, and transcriptional responses were measured to identify the key genes regulating phenotypic changes after single or multiple drops. A progressive reduction of the quantum yield of PSII revealed a lower electron transport rate in leaves subjected to one or more drops, which may indicate the onset of energy shortage, potentially caused by limited ATP availability that constrains both leaf movement and photosynthesis. The transcriptomic profiles revealed larger differences when plants were subjected to multiple drops than to a single drop, with respect to unstressed controls. Interestingly, following a single drop, the majority of up-regulated genes were associated with the flavonoid biosynthetic pathway. After multiple drops, however, genes associated with biotic and abiotic stress resistance pathways were predominantly up-regulated. These findings provide new insights into the gene regulatory networks driving stress-induced movements in M. pudica leaves and lay the groundwork for developing sustainable strategies for plant stress defense.

Effect of bioactive compounds released from Brassicaceae defatted seed meals on bacterial load in pig manure - Luisa Ugolini; Donatella Scarafile; Roberto Matteo; Eleonora Pagnotta; Lorena Malaguti; Luca Lazzeri; Monica Modesto; Alice Checcucci; Paola Mattarelli; Ilaria Braschi (Environmental Science and Pollution Research, 2021)
Animal manure application to soils is considered to be one of the main cause of antibiotic and bacterial pathogen spread in the environment. Pig livestock, which is the source of one of the most used fertilizer for cultivated land, is also a hotspot for antibiotics and antibiotic-resistant bacteria. Besides harsh chemical and physical sanitization treatments for the abatement of antibiotics and bacterial load in livestock waste, more sustainable and environmentally friendly strategies need to be considered. In this context, the use of natural substances which are proved useful for pest and disease control is currently under exploration for their role in the reduction of bacterial pathogen population. Among these, plants and derived products from the Brassicaceae family, characterized by the presence of a defensive glucosinolate-myrosinase enzymatic system, have been successfully exploited for years in agriculture using the so-called biofumigation technique against crop diseases. Although the application of biofumigation to suppress a range of soil borne pests has been well documented, no studies have been examined to reduce bacterial population in animal waste. In the present study, the release and the antibacterial activity of bioactive compounds deriving from different Brassicaceae defatted seed meals against pathogens and bacterial population in pig manure is addressed. Rapistrum rugosum and Brassica nigra defatted seed meals were found to be the most active products against tested pathogens and able to significantly reduce the bacterial load in the manure.